European Integration and Labour Migration - d'Artis Kancs; Julia Kielyte (Economics and Econometrics Research Institute (EERI), 2010)
The present paper studies how European integration might affect the migration of workers in the enlarged EU. Unlike the reduced-form migration models, we base our empirical analysis on the theory of economic geography à la Krugman (1991), which provides an alternative modelling of migration pull and push factors. Parameters of the theoretical model are estimated econometrically using historical migration data. Our empirical findings suggest that European integration would trigger selective migration between the countries in the enlarged EU. In the Baltics, Lithuania would gain about 7.25% of the total work force. In the Visegrád Four, the share of the mobile labour force would increase the most in Hungary, 8.35%, compared to the pre-integration state. Our predictions for the East-West migration are moderate and lower than those of reduced-form models: between 5.44% (from the Baltics) and 3.61% (from the Visegrád Four) would emigrate to the EU North. Because migrants not only follow market potential, but also shape the region's market potential, the long-run agglomeration forces are sufficiently weak to make a swift emergence of a core-periphery pattern in the enlarged EU very unlikely.
Keywords: F12; L11; R12; R23; 330; New economic geography; Market potential; Labour migration; Economic integration